2019
DOI: 10.1038/s41586-019-1433-7
|View full text |Cite
|
Sign up to set email alerts
|

Memory editing from science fiction to clinical practice

Abstract: Science fiction notions of altering problematic memories are starting to become reality as techniques emerge through which unique memories can be edited. Here we review memory-editing research with a focus on improving the treatment of psychopathology. Studies highlight two windows of memory vulnerability: initial storage, or consolidation; and restorage after retrieval, or reconsolidation. Techniques have been identified that can modify memories at each stage, but translating these methods from animal models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 101 publications
4
93
0
4
Order By: Relevance
“…We found that both were significantly heritable, though the continuous (total symptom) trait was the most heritable, and therefore the most informative with regard to biological inference. Importantly, partitioned heritability analyses of that trait indicated preferential expression of SNPs in frontal (BA9) and anterior cingulate cortex (BA24), consistent with prevailing neural circuit theories of PTSD pathophysiology (Shalev et al, 2017) that emphasize function of these regions and their connections with limbic cortex in the regulation of emotion and extinction of fear memories (Dunsmoor et al, 2015;Phelps and Hofmann, 2019).…”
Section: Discussionsupporting
confidence: 68%
“…We found that both were significantly heritable, though the continuous (total symptom) trait was the most heritable, and therefore the most informative with regard to biological inference. Importantly, partitioned heritability analyses of that trait indicated preferential expression of SNPs in frontal (BA9) and anterior cingulate cortex (BA24), consistent with prevailing neural circuit theories of PTSD pathophysiology (Shalev et al, 2017) that emphasize function of these regions and their connections with limbic cortex in the regulation of emotion and extinction of fear memories (Dunsmoor et al, 2015;Phelps and Hofmann, 2019).…”
Section: Discussionsupporting
confidence: 68%
“…If this pathway is silenced, however, even the memory of a very aversive event displays plasticity and can undergo destabilization upon recall. Reconsolidation is a critical biological feature to maintain memory's relevance in guiding behavior 8,37 , and reconsolidation-targeted treatments provide a unique opportunity to weaken pathological fear memories 38,39 . Nonetheless, learning strength is a parameter which acts to prevent reconsolidation from happening, therefore curbing the efficacy of reconsolidation treatments in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…De tous temps, des substances chimiques ont été capables de modifier le comportement humain (alcool à petite échelle, puis drogues plus ou moins naturelles) [15]. De nos jours, le développement rapide des neurosciences a non seulement permis une cartographie précise du cerveau et une identification des zones impliquées dans la mémorisation, la prise de décision, le sens moral [16] mais également le moyen de modifier le comportement d'un individu [17]. Le balbutiement de ces travaux est expliqué dans l'excellent livre de Antonio R. Damasio [18].…”
Section: Homme Augmenté (Modifié) Dans Sa Conscienceunclassified
“…Ils sont capables de rendre quelqu'un de phobique, normal, quelqu'un de timoré, sûr de lui ; et surtout ils sont capables de changer la perception d'un évènement par un individu. Ce dernier peut devenir exempt de tout sens moral, sans aucune empathie et incapable d'analyser un évènement du point de vue moral [17]. Est-ce qu'une personne privée de sens moral par un tiers et incapable de discerner le bien du mal est toujours une personne humaine ?…”
Section: Homme Augmenté (Modifié) Dans Sa Conscienceunclassified